Risk factors associated with tilapia and pangasius diseases - Faruk, MAR; Rahman, N; Patwary, ZP (Journal of the Bangladesh Agricultural University, 2017)
Tilapia (Oreochromis niloticus) and pangasius (Pangasianodon hypophthalmus) are currently very important and popular species for aquaculture inBangladesh. They are cultured commercially in high stocking densities which are accompanied by several risk factors leading to disease outbreaks. The present study was carried out to investigate diseases of these two species under farming condition with special emphasis on risk factors analysis and their health management strategies. Data were collected through questionnaire interview and focus group discussion with farmers. Altogether 50 farmers were interviewed of which 25 were tilapia farmers and 25 were pangus farmers in Trishal upazila of Mymensingh district. Possible risks were assessed using certain parameters like season of disease occurrence, presence of predators in farms, contact with livestock, maintenance of farm hygiene, sharing of farming tools, feeding of fish and pond management measures. It was found that presence of predatory birds, maintenance of good farm hygiene, sharing of tools, increased stocking densities and improper pond management were the major risks of disease outbreak. The most prevalent clinical signs of diseased fish included anal protrusion and red spot on body surface in case of pangus while pop and red eye and gas problems were common in both pangasius and tilapia. Generally, pangus were found more susceptible to disease than tilapia. Predatory birds were a big problem in the study area. They act as a potential carrier of infectious organisms among farms from farm to farm. J. Bangladesh Agril. Univ. 15(2): 325-331, December 2017